CULTURAL COMPETENCE AND CULTURAL INTELLIGENCE OF THE MODERN SPECIALIST - Білицька, Вікторія Миколаївна (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2020)
The article is concerned with the competencies of the modern specialist, namely cultural competence and cultural intelligence; it analyzes the structural components of the concepts and approaches and their involvement in the educational process. The objective of the article is the analysis and generalization of the modern specialist’s "cultural competence" and "cultural intelligence" concepts in the pedagogical aspect. The complex of interrelated research methods has been used to solve the tasks set and to achieve the objective of the research, for example, the analysis and generalization, structural-functional method to clarify the essence and highlight structural components of the cultural competence, a method of logical and semantic analysis to clarify the content of the "cultural competence" and "cultural intelligence" concepts, a systematic method to determine the interaction and interrelation of the components of cultural competence in the framework of modern specialist’s competencies. The article refers to the studies of recent decades that have made significant progress in the analysis of cultural differences and their successful overcoming, thus laying the foundation for the synthesis of the abilities that distinguish the "culturally competent" professional from the general public, and their assessment. An individual’s cultural competency takes the form of key competence, which enables him or her to understand and freely use the full range of competencies and competences acquired in socio-cultural and social, institutional and conventional norms and regulators of behaviour in mobile social communication, including in different languages. The cornerstone of the competence is culture, which is not only the result of human activity, but also represents historically established ways of working, and recognized behavioural patterns, manner of communication, ways and techniques of the expression of feelings, as well as the level of thinking ability. The cultural intelligence allows a person to function effectively, achieve significant results and is a prerequisite for solving various problems in the environmental, political, socio-economic and cultural development of the humankind.